RANCANGAN MAKET PRESENTASI LANSEKAP JAM GADANG DI BUKITTINGGI - TOMMY TRIVIYANDA, Drs. Ir. Heldi, M.Si Dra. Zubaidah, M.Sn (Serupa The Journal of Art Education, 2014)
West Sumatra is one province that has many historic towns such as Padang Sawalunto, Payakumbuh and Bukittinggi, with the historic buildings of the colonial Dutch colonial heritage. Form one of the cultural assets of concern is the relic of the Dutch colonial history of "Jam Gadang" as a landmark that is located in the center of Bukittinggi as a travel destination, local and foreign.The city governmentin order to curb traers sell the Clock Tower in the park, so that tourists feel comfortable in the Clock Towerpark. Sulistio as sessthe park "Jam Gadang" is not unlike the market where many vendors selling impromp. End of Pekanbaru named Lukman said he was disappointed with the condition of the park"Jam Gadang" chaotic. Because, vendors selling impromp left that is not managed properly.On paper this looks a scale model of a garden design which consists of several elements that are processed and organized, thus presenting a beautiful design mockups. create works through processes form process accord an cewith the value ofthe function and structure ofthe actual location, and also the techniques usedin the creation process, the harmony of colors also taken in to account.Final work is intended that the Government and the community care about the beauty and cleanliness of the landscape "Jam Gadang". Provide input to the city government to pay more attention to landscape Bukititnggi "Jam Gadang" in Bukittinggi.Kata Kunci : Rancangan, Maket, Lansekap, Jam Gadang